At the edge of the orchard [compact disc, unabridged] : a novel - Chevalier, Tracy; Bramhall, Mark; Huber, Hillary; Heyborne, Kirby; Morris, Cassandra, 1982- (Penguin Audio ; Books on Tape, 2016)
James Goodenough, whose family had originally settled in Connecticut from England brings his family to Ohio to carve out a new life for them in the Black Swamp in 1838. Fifteen years later their youngest son, Robert, who has been running west to escape his memories of the past, takes solace in a very different kind of tree--the redwoods and sequoias of California. But Robert's past catches up with him and he's forced to confront what he's running from and work out for himself that you can't run forever.